The Development of Active Learning Based on a Service-Learning Model to Enhance Public Consciousness of Undergraduate Students - Wongklang, Piyanoot; Sovajassatakul, Thanongsak (Scholar: Human Sciences, 2021)
The objective of this study was to develop active learning based on service learning model to enhance public consciousness of undergraduate students studying educational technology. A total of 7 experts were employed to design the instruction in terms of teaching and learning management, information technology, and educational innovation. Moreover, they evaluated the appropriate of the design and provided suggestions. The research instruments used were: (1) a draft of active learning based on service learning model. (2) an appropriate evaluation form. Data analysis was done by mean (), standard deviation (S.D), and content analysis. From the results research, the draft of development learning model was found to be highly appropriate ( = 4.45 SD = 0.513). A model for learning management in 5 steps was obtained, including Stimulation, Investigation, Action, Reflection, and Evaluation. The factors that were found to promote learning included local community and computer-supported collaborative learning.